2001
DOI: 10.1086/322135
|View full text |Cite
|
Sign up to set email alerts
|

The Optical/Infrared Astronomical Quality of High Atacama Sites. I. Preliminary Results of Optical Seeing

Abstract: The region surrounding the Llano de Chajnantor, a high-altitude plateau in the Atacama Desert in northern Chile, has caught the attention of the astronomical community for its potential as an observatory site. Combining high elevation and extremely low atmospheric water content, the Llano has been chosen as the future site of the Atacama Large Millimeter Array. We have initiated a campaign to investigate the astronomical potential of the region in the optical/infrared. Here we report on an aspect of our campai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 10 publications
0
15
1
Order By: Relevance
“…Furthermore, a scale height of the water vapour profiles on the Chajnantor area can be deduced from the quartiles of the plateau and the "Cerro". With the satellite measurements, we computed a 1/e scale height h e of the order of 1.1 km that is in a good agreement with measurements from Giovanelli et al (2001). The PWV quartiles at the South Pole were computed at saturation from radio-sounding balloons over a period of 40 years (see Chamberlin 2002).…”
Section: Iasi (Infrared Atmospheric Soundingmentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, a scale height of the water vapour profiles on the Chajnantor area can be deduced from the quartiles of the plateau and the "Cerro". With the satellite measurements, we computed a 1/e scale height h e of the order of 1.1 km that is in a good agreement with measurements from Giovanelli et al (2001). The PWV quartiles at the South Pole were computed at saturation from radio-sounding balloons over a period of 40 years (see Chamberlin 2002).…”
Section: Iasi (Infrared Atmospheric Soundingmentioning
confidence: 67%
“…Cerro Chajnantor and Chajnantor Plateau were extensively studied (see Giovanelli et al 2001) and the PWV quartiles between 2006 and 2010 can be found in Radford (2011). The values deduced from opacity measurements at 225 GHz are 0.61 mm (25%), 1.08 mm (50%), and 2.01 mm (75%) for the plateau; and 0.33 mm (25%), 0.61 mm (50%), and 1.36 mm (75%) for Cerro Chajnantor.…”
Section: Iasi (Infrared Atmospheric Soundingmentioning
confidence: 99%
“…The characteristic Greenwood Frequency is 2π/t 0 . The values for the atmospheric constant (τ 0 = 0.021s,V 0 = 15m · s −1 , and r 0 = 10cm) are taken from observations made at the Large Atacama Telescope site by Giovanelli et al 2,9 Substituting the values and using the previously defined shift operators we have, 47.831w(s 1 , s 2 , t) + 1.35104w(s 1 , s 2 , t) + . .…”
Section: Modelling Of the Deformable Mirrormentioning
confidence: 99%
“…Núñez et al [4] was compared two DIMMs units during 14 nights at SPM (San Pedro Martir), the first DIMM is that used at the Observatorio Astronomico Nacional at SPM and the second DIMM is a NOAO RoboDIMM unit (RoD) is that of CTIO (Cerro Tololo Inter American Observatory). Giovanelli et al [5] was carried out an other comparison during two nights in 2000 October between ESO-DIMM-C1 and CTIO DIMM, The two devices were different in both hardware and software but the comparison between the data sets has shown a good agreement. Hach et al, [6] was carried out another cross calibrationin in July-August 2004 at Oukaimeden Observatory for DIMM and DIMMAR instruments( tow DIMMs developed in Oukaimeden Observatory).…”
Section: Introductionmentioning
confidence: 99%